Analisis Quality of Service (QoS) Performa Jaringan Internet Wireless LAN PT. Bhineka Swadaya Pertama - Elin Panca Saputra; Andi Saryoko; Mawadatul Maulidah; Nadiyah Hidayati; Sopiyan Dalis (Universitas Bina Sarana Informatika, 2023)
In the current era of digitalization, the use of ISPs or Internet Service Providers is very commonly used in the business world because they have effective and flexible services because they can be used wirelessly or without cables to meet their needs. Currently, there are many connection service providers in Indonesia, First Media is one of several existing ISPs. First Media offers a stable and fast internet connection, unlimited internet without quota and unlimited download speed of up to 10 Mbps and 768 Kbps upload speed, and has several other features that can be used wirelessly or without cable as needed. The use of wireless-based networks in general must have a service standard known as Quality Of Service (QOS). QoS is used in measuring the performance of an internet network in order to provide even better service. In conducting internet network analysis, Quality Of Service (QOS) parameters are needed which include packet loss, delay/latency, Throughput, Jitter, it will produce information in the form of network analysis results and the results of this analysis can be used as recommendations so that in the future it can develop internet networks to be more good again and can support the addition of other services. The purpose of this research is to analyze the Quality Of Service (QOS) of the internet network at PT. Bhineka Swadaya Pertama and knowing the quality of the Wireless Lan internet network at